Exploring the potential of Indonesian iron sand in the formation of iron nitride for magnetic applications - Indra Sidharta; Rakhasoni Firman Syah; Sutikno Sutikno; Darminto Darminto; Abdullah Shahab (Mechanical Engineering for Society and Industry, 2025)
Iron nitride is a transition metal material that exhibits ferromagnetic properties at room temperature, making it a suitable candidate for use in Soft Magnetic Composites (SMC) applications. Previous research showed that iron nitride can be synthesized using nano-sized iron oxide powder derived from processed natural iron sand through gas nitriding. Considering the abundance of iron sand in Indonesia, there is a need to carry out an investigation related to iron sand-based SMC. Therefore, this research aims to synthesize iron nitride material using the abundant natural iron sand discovered in Indonesia. This study used iron oxide material synthesized from locally obtained natural iron sand, in the form of Fe3O4 and Fe2O3. Iron oxide undergoes coprecipitation and was subsequently exposed to the gas nitriding process with a holding time of 4 hours and a gas flow of 150 mL/min in NH3 gas. The results show that iron nitride is formed after nitriding of iron oxide powders, and the phases formed include ε-Fe3N and γ’-Fe4N. The synthesized material exhibits soft magnetic properties, with saturation magnetization values ranging from the highest at 75.41 emu/g and the lowest at 18.9 emu/g.